PELAKSANAAN PERJANJIAN OLEH PT. SANLING SAWIT SEJAHTERA PADA DESA RIMPIAN KECAMATAN LUBUK BATU JAYA KABUPATEN INDRAGIRI HULU - Anggun Pratiwi; Mardalena Hanifah; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Agreements can be made in written or oral form, and it is not uncommon to findagreements made secretly. Oral agreements occur a lot in social life, oral agreementsare the realization of the principle of consensualism, which comes from the Latinconsensus. This means that in principle an agreement that arises has been born fromthe moment the agreement is reached. The formulation of the problem posed is how toimplement the agreement at PT. Sanling Sawit Prosperous Rimpian Village, Lubuk BatuJaya District, Indragiri Hulu Regency and how the efforts in implementing the PTagreement. Prosperous Sanling Sawit in Rimpian Village, Lubuk Batu Jaya District,Indragiri Hulu Regency.The type of legal research is sociological, which in this research is carried out bygoing directly to the field to collect primary data through interviews with the partiesinvolved in this case, namely Area Supervisor, HRD PT. Sanling Sawit Sejahtera, Headof SPSI, Employee of PT. Prosperous Sawit Sanling, Member of BPD, Head of RT,Community. This research uses a descriptive method. The nature of this research isdescriptive.The result of this research is the implementation of the agreement between PT.Sanling Sawit Sejahtera with the Rintian Village community showed that the agreedagreement was not implemented because the company had defaulted where thecompany should have repaired and maintained the road by providing funds inaccordance with the agreement in the agreement Number: 001/SSS/KT-KA II/VII/2022. Legal efforts in implementing the PT agreement. Sanling SawitSejahtera in Rintian Village, which has been carried out by the community, in the formof initial legal remedies such as demonstrations by placing banners along the roadcontaining rebellion and disappointment from the community. With the damage to roadsand bridges, the community rebelled in the form of demonstrations and the installationof banners along the roads containing anger and disappointment.Keywords: Agreement, Company, Responsibility